Come On, Be Good! It's Nearly Over... .German and Romanian Forms of Address in Communication between Pets, Vets or Pet Owners and the Animal to Be Treated - Fierbinţeanu, Ioana Hermine (Universitatea Transilvania Brasov, 2024)
The form of address is one of the most important features for making contact in society. Dictionaries and grammars provide very little information on the subject, so in each situation, learners must consider factors such as Communication situation, age of interlocutors, social status, and official nature of the situation to make an appropriate decision. Based on recordings and interviews, I try to ascertain what pronominal and nominal forms of address occur in German and Romanian veterinary practices. In addition to the first names, pet names and nicknames with which the pets (dogs, cats, hamsters, cows, ducks, etc.) are addressed by the pet owners and the veterinarians, nominal phrases such as Guter Junge! or Un băiat cuminte! (A good boy) appear. In addition to the forms of address mentioned above, Romanian also has reverse forms of address and interjections of address.
Keywords: Forms of Address; Interjections; Nominal Address; Veterinary Practice; Veterinarian; Pet Owner; Pet